Empowering the Global South through localized innovation: an ai assistant for economic collaboration - Garin, Artyom; Kostyrkin, Aleksandr (InterAção, 2025)
Amid global instability and growing technological dependency, the need for technological sovereignty—the capacity of nations to independently develop and control critical technological solutions—has become increasingly urgent. For Global South countries, this is not merely a matter of national resilience but also a new opportunity to strengthen multilateral cooperation. Evidence suggests that collaborative initiatives in information technology (IT) among Global South countries could enhance systemic resilience and foster more equitable development. This article examines case studies demonstrating how the pursuit of technological sovereignty catalyzes partnerships between developing nations and explores locally adapted solutions designed to streamline science-to-business collaboration. This study examines the AI-assistant developed by the Institute of Oriental Studies of the Russian Academy of Sciences (IOS RAS) and hosted on Yandex Cloud, demonstrating how such tools are transitioning into perspective structure for cross-border economic cooperation.